The Influence of Internal Organizational Environment, Transformational Leadership, and Work Motivation on the Effectiveness of Planet Ban Organization - Sausan, Rianovita; Zurnali, Cut (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze the influence of internal organizational environment, transformational leadership, and work motivation on organizational effectiveness at Planet Ban. This study uses a survey method with a sample of 131 people with a random sampling technique . The data collection technique used a questionnaire that had been tested for validity and reliability. The data analysis technique used the Partial Least Square (PLS) version 4 application. by evaluating the outer model, inner model, and path analysis tests . The results of the study provide the following conclusions: (1) The internal environment of the organization influences the effectiveness of the organization; (2) Transformational leadership influences the effectiveness of the organization; (3) Work motivation influences the effectiveness of the organization; (4) The internal environment of the organization, transformational leadership, and work motivation simultaneously influence the effectiveness of the organization. These findings provide theoretical contributions in organizational management as well as practical recommendations for Planet Ban management to strengthen the work environment, implement the right leadership style, and motivate employees effectively